Las heladas como resultado del cambio climático y su consecuencia en la agricultura del cantón Salcedo, Cotopaxi, período 1981-2010. - Moreno Navarrete, Polivio Oswaldo (2013)
The problematic of climate worldwide was evidenced during the first World Conference the climate of 1979. So the change in global temperature effect on planetary climate events, with a greater presence and frequency to extreme levels as frost. For this reason, the Ecuador has historically supported this type of phenomena. It ranging from the atmosphere behavior to the environment and changes in warmth, climate change, high and low temperatures. Therefore, the present study in the Salcedo canton seeks to define the historical processes of the climate phenomenon, through the description of the environment of the canton and the analysis of the meteorological records of the INAMHI in their climatological yearbooks of thirty years in the period 1981-2010. Observed for each decade, a decrease in the number of frost in function of time, whereas the periods from 1981-1990: there were 9.3 frost on average; well as in the period between 1991 and 2000: took place 8.3 frozen on average. While in the 2001-2010 Decade: arose 7.0 frost on average, analyzed and compared with other scientific research, data once match national reports on climate change, with an increase of the average temperature of up to 0.5 ° C, as well as decreases in the Central High land and South of the Ecuador. Being affected around 12,218 hectares, of which calculated on the basis of the subsidies granted, there are annual economic losses of about 2419.164 USD.